Katingan regency regional government synergy in mitigating forest and land fires - Budiono, Teguh; Kristanto, Kiki; Wardhani, Novea Elysa (Institute Of computer Science (IOCS), 2025)
Forest and land fires (karhutla) in Katingan Regency, Central Kalimantan, are a serious issue that occurs almost every year, particularly in peatland areas. Karhutla not only causes ecological damage, such as ecosystem degradation and loss of biodiversity, but also has social and economic impacts, including health problems caused by haze, economic losses, and increased carbon emissions that accelerate global warming. Peatland areas are of particular concern due to their large carbon reserves, which, when burned, release significant emissions. The issue addressed in this study is the effectiveness of the synergy between Katingan regency Local Government in forest and land fire mitigation, which still faces challenges, particularly in coordination between central and local governments, budget constraints, and suboptimal resources in fire control in vulnerable areas such as Katingan. This study evaluates the synergy between local governments, communities, and stakeholders in mitigating karhutla using a juridical-empirical approach. Although various policies have been implemented, such as regional regulations and the construction of canal blocks, their implementation faces challenges, including geographical factors, limited budgets, a lack of trained human resources, and weak law enforcement. The findings of this research indicate that the mitigation of forest and land fires in Katingan regency is still constrained by limited resources and coordination, hence stronger synergy among stakeholders is required. Hence, a more integrated approach and collaboration among all parties are needed to develop effective mitigation strategies, preserve ecosystem sustainability, and support the achievement of Sustainable Development Goals (SDGs).